Teacher as a Role Model to Meet Global Challenges - Suchitra, Dr. P. (IJRDO - Journal of Social Science and Humanities Research, 2017)
As a result of quick economic growth, influence of western culture, over mechanization, urbanization and craving for materialistic life there has been a loss of values and of the value system at the individual level and in the society as a whole. History speaks and universally accepted, the teachers are unchallenged custodian of the society and embodiment of evolutions and revolutions of the world. The kingpin in the schooling process is the teacher. If the teacher is personally committed to the values and practices them in his/her own life, the students will imbibe the values for which teacher stands. It is for this reason only those teachers who leave deep impact on their students are remembered and also revered. Therefore, if values have to be nurtured in children it would be crucial that their teachers function as role models. The participation of teachers in the formulation and implementation of educational plans can yield rich dividends, especially in institutional planning and programmes of qualitative improvement. Several of the community improvement programmes and school programmes such as improvement of text books, adoption of better methods of teaching and evaluation, intensive utilization of available facilities, maintaining contact with community, individual guidance to students, inculcation of social and moral values etc do not need much investment in physical or monetary terms. But their success depends essentially upon the competence of the teachers, their sense of dedication and their identification with the interests of the students committed to their care. But unless they make every effort to cultivate these skills and values they shall not be able to participate effectively in educational programmes and to discharge their responsibility to students and the society.